Early diagnosis of tuberculosis in the health services in different regions of Brazil El diagnóstico oportuno de la tuberculosis en los servicios de salud de varias regiones de Brasil Diagnóstico oportuno da tuberculose nos serviços de saúde de diversas regiões do Brasil - Tereza Cristina Scatena Villa; Maria Amélia Zanon Ponce; Anneliese Domingues Wysocki; Rubia Laine de Paula Andrade; Tiemi Arakawa; Beatriz Estuque Scatolin; Maria Eugenia Firmino Brunello; Aline Ale Beraldo; Lucia Marina Scatena; Aline Aparecida Monroe; Reinaldo Antonio da Silva Sobrinho; Lenilde Duarte de Sá; et al. (Universidade de São Paulo, 2013)
OBJECTIVE: To analyze the infected person's first contact with the health services, for the early diagnosis of tuberculosis (TB) in different regions of Brazil. METHOD: a cross-sectional study undertaken in 6 municipalities in the South-east, South and North-east regions of Brazil. Data collection involved secondary sources and interviews with the patients. The data was analyzed using descriptive techniques and multiple correspondence factor analysis. RESULTS: Primary Health Care (PHC) presented the longest time to diagnosis and the lowest proportion of diagnoses. The services associated with diagnosis in the first consultation were the specialized services and the Tuberculosis Control Programs, which offer consultations and tests on-site. CONCLUSION: For the control of TB, it is necessary to organize the work in an integrated way between the different services' teams. In Primary Health Care, it is also necessary to observe the extent of incorporation and sustainability in the implementation of these actions into the health services' daily practice. OBJETIVO: Analizar el primer contacto del paciente con los servicios de salud para el diagnóstico oportuno de la tuberculosis (TB) en diferentes regiones de Brasil. MÉTODO: Estudio transversal en seis ciudades en el sudeste, sur y noreste. La recolección de datos utilizó fuentes secundarias y entrevistas con los pacientes. Los datos fueron analizados utilizando técnicas descriptivas y el análisis factorial de correspondencias múltiples. RESULTADOS: La Atención Primaria obtuve menor proporción de diagnósticos y mayor tiempo. Los servicios asociados con el diagnóstico en la primera visita fueron los servicios especializados y los Programas de Control de la Tuberculosis, que ofrecen consultas y exámenes in situ. CONCLUSIÓN: Es necesaria la organización del trabajo integrado entre los equipos de los diferentes servicios para las acciones de control. En la Atención Primaria, es necesario también observar el grado de desarrollo y sostenibilidad en la aplicación de estas medidas a la práctica diaria de los servicios. OBJETIVO: analisar o primeiro contato do doente com os serviços de saúde para o diagnóstico oportuno da tuberculose (TB), em diferentes regiões do Brasil. MÉTODO: trata-se de estudo de coorte transversal, em 6 municípios das Regiões Sudeste, Sul e Nordeste. Para a coleta utilizaram-se fontes secundárias e entrevista com os doentes. Os dados foram analisados por meio de técnicas descritivas e análise fatorial de correspondência múltipla. RESULTADOS: a Atenção Primária à Saúde apresentou maior tempo e menor proporção de diagnósticos. Os serviços associados ao diagnóstico, na primeira consulta, foram os serviços especializados e os Programas de Controle da TB, que oferecem consulta e exames no próprio local. CONCLUSÃO: faz-se necessária a organização do trabalho de forma integrada, entre as equipes dos diferentes serviços, para as ações de controle da TB. Na Atenção Primária à Saúde, é preciso ainda observar o grau de incorporação e sustentabilidade na execução dessas ações à prática diária dos serviços.